Analisis Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Segi Empat dan Segitiga di Kelas VIII SMP - Betti Triwarsana; Marhadi Saputro (LPD IKIP PGRI Pontianak, 2024)
This study aims to analyze the mathematical creative thinking ability of grade VIII students in solving quadrilateral and triangle problems in one of the swasta junior high schools in Pontianak. This research used descriptive method with qualitative approach. Data were collected through essay tests and interviews to provide an overview of students' mathematical creative thinking ability. The results showed that 21.28% of students were in the low ability category, with scores below the difference between the mean and standard deviation of students' scores. In the medium category, 61.7% of students scored above or equal to the low group score criteria but below the high group score criteria. Meanwhile, 17.02% of students were in the high category, with scores above or equal to the sum of the mean and standard deviation of student scores. Analysis of the indicators of creative thinking ability shows that students have very good abilities in the indicators of fluency, flexibility, and elaboration. However, in the originality indicator, students are still in the good category. These findings indicate the need for improvement in the originality aspect of students' creative thinking to achieve more optimal results in mathematical problem solving.